High security Iris verification system based on random secret integration - SIEWCHIN, C; BENGJIN, A; CHEKLING, D (2006)
A dual-factor authentication methodology coined as S-Iris Encoding is proposed based on the iterated inner-products between the secret pseudo-random number and the iris feature, and with thresholding to produce a unique compact binary code per person. A thresholding method is devised to exclude the weak inner-product during the encoding process, and thus contribute to the improvement of performance. S-Iris Encoding is primary formulated based on the cancelable biometrics principle to protect against biometrics fabrication. The problem could be rectified by S-Iris code through the token replacement so that a new code can be generated instantly just as a new credit card number can be issued if the old one is compromised. Besides that, S-Iris code is non-invertible and can only contribute to the authentication process when both genuine biometrics template and token are presented. By applying S-Iris Encoding with weak inner-product exclusion, the original iris feature length can be greatly reduced to around 4% of the original size and a 0% of equal error rate (EER) can be attained in CASIA Iris image database. (c) 2006 Elsevier Inc. All rights